2018
DOI: 10.1097/hnp.0000000000000277
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in a Graduate Nursing Curriculum

Abstract: This study evaluated a mindfulness-based stress reduction intervention for graduate nursing students. Forty-four participants engaged in 20 weekly, 1.5-hour sessions of mindfulness training. There were no statistically significant effects on participants' stress levels or quality of life, yet there was a statistically significant increase in overall mindfulness (P < .05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Perhaps the observed stress was caused by heavy workload and credits. In another study, nursing students after MBSR intervention showed an increase in mindfulness, but no effect on stress or the quality of life was noted [48]. The timing of such interventions seems to be crucial.…”
Section: Medical Studentsmentioning
confidence: 91%
“…Perhaps the observed stress was caused by heavy workload and credits. In another study, nursing students after MBSR intervention showed an increase in mindfulness, but no effect on stress or the quality of life was noted [48]. The timing of such interventions seems to be crucial.…”
Section: Medical Studentsmentioning
confidence: 91%
“…Given these concerns, accelerated online degree programs in nursing can benefit from utilizing MBT within the curriculum, delivering it in various strategies that can be beneficial for students. A randomized controlled study by Plummer et al (2018) assessed mindfulness-based stress reduction intervention for graduate nursing students. Forty-four participants engaged in 20 weekly 1.5-hour sessions of mindfulness training.…”
Section: Mindfulness In Nursing Educationmentioning
confidence: 99%
“…Mindfulness is defined as being present in the current moment 36 in mind and body to reduce stress and anxiety, improve focus, and decrease burnout. 37 Promoting positivity through mindfulness moments increases resilience.…”
Section: Introductionmentioning
confidence: 99%